Interrupted education: the criminal justice system and educational progress of young offenders, 2008-2009 - Wilson, Anita (UK Data Service, 2011)
Interrupted Education: the Criminal Justice System and Educational Progress of Young Offenders, 2008-2009 investigated the impact of the criminal justice system on the lives of young men in custody. Building on their educational histories, the study looked at whether their progress was subsequently exacerbated or ameliorated by the system. The project also explored how these young people re-deployed literacy skills as they negotiated prison bureaucracy. The research was undertaken over 14 months, centring on the experience of young men in one prison. The research centred on one establishment, engaging the whole prison, but drawing particularly on the rich narratives of selected young people. Data collected and analysed were from a pre-existing database of juvenile offenders’ experience of education; questionnaires completed by 618 young men in custody; a further 40 in-depth interviews with young prisoners; and a number of ad-hoc cumulative dialogues with a range of staff. (The data available from the UK Data Archive only includes the quantitative questionnaire data and does not include any qualitative interview transcripts.)